Theoretical and practical bases of work on the portrait in oil painting as the basis of mastering the professional and creative knowledge (Pedagogy of Higher and Secondary Education, 2009)
The article describes the ways of formation of theoretical and practical bases of work on the portrait.
Keywords: portrait; artistic image